2015
DOI: 10.17264/stmarieng.6.111
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical CD10 Expression is Useful for Differentiating Malignant Melanoma from Benign Melanocytic Nevus

Abstract: Malignant melanoma (MM), an aggressive skin neoplasm, can be difficult to differentiate histologically from benign melanocytic nevi (BMN). Although immunohistochemical analysis could facilitate diagnosis of MM, markers that discriminate between benign and malignant lesions have not yet been established. However, CD10 expression is associated with MM progression. We immunostained 36 MM and 50 BMN specimens for CD10 to evaluate whether CD10 immunostaining could distinguish between BMN and MM tumors. In the 36 MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(40 reference statements)
2
0
1
Order By: Relevance
“…These results, although similar to but, were much higher than those stated by Oba et al [7], 2011, who like us found that CD10 positivity was seen in most of melanoma cases but with lower percentage (53%). Unlike our results, less CD10 prevalence was reported by the studies done by Hoshikawa et al [6], 2015 (47%), and Bilalovic et al [8], 2004 (22%). The higher CD10 expression in our study could be related to our smaller sample size.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…These results, although similar to but, were much higher than those stated by Oba et al [7], 2011, who like us found that CD10 positivity was seen in most of melanoma cases but with lower percentage (53%). Unlike our results, less CD10 prevalence was reported by the studies done by Hoshikawa et al [6], 2015 (47%), and Bilalovic et al [8], 2004 (22%). The higher CD10 expression in our study could be related to our smaller sample size.…”
Section: Discussioncontrasting
confidence: 97%
“…Most of our studied BMN cases were CD10 negative (20 cases, 83.3%), all the remaining positive cases showed +1 score. In agreement with our results, Hoshikawa et al [6], 2015, studied 50 BMN cases all were CD10 negative and Oba et al [7], 2011, who studied 40 BMN cases showing positive CD10 staining in only 10%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation